2023
DOI: 10.3390/met13030520
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PEO Treatment in a Ta-Rich Electrolyte on the Surface and Corrosion Properties of Low-Carbon Steel for Potential Use as a Biomedical Material

Abstract: Fe-based materials have extensive applications in the building and automobile industries due to their excellent mechanical properties and low cost. However, their biomedical employment is restricted by the corrosion propensity when in contact with bodily fluids. In this study, single-step Plasma Electrolytic Oxidation, PEO, treatment in Ta-rich electrolyte was used, for the first time, to improve the corrosion resistance of low-carbon steel SAE 1020 for possible use as device implants. The effect of the applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similar results were obtained for the other samples of each PEO treatment condition (see Figures S1-S5 in Supplementary Material). Marcuz et al [20] found similar curves during PEO treatment on low-carbon steel, which was related to the oxidative reaction and plasma discharges that occurred on the surface.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Similar results were obtained for the other samples of each PEO treatment condition (see Figures S1-S5 in Supplementary Material). Marcuz et al [20] found similar curves during PEO treatment on low-carbon steel, which was related to the oxidative reaction and plasma discharges that occurred on the surface.…”
Section: Resultsmentioning
confidence: 82%
“…The open-circuit potential (OCP) was previously measured for 1 h. Then, the potentiodynamic polarization (PDP) test was performed from −1 to 2 V vs. OCP, with a scan rate of 1 mV•s −1 and step size of 1 mV. The obtained results were analyzed using NOVA 2.0 ® software (version 2.1.5), which evaluated the corrosion potential (E corr ), corrosion current density (i corr ), and polarization resistance (R p ) using Tafel's extrapolation method and the Butler-Volmer equation [20]. Finally, the electrochemical impedance spectroscopy (EIS) test was performed in the frequency range of 100 kHz to 100 mHz with ten points per decade and a signal amplitude of V rms = 10 mV.…”
Section: Sample Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Metal materials are the most widely used materials in industrial and agricultural production. Among many metal materials, mild steel is widely used in automobile, ship and machinery manufacturing because of its advantages of good formability, excellent plasticity and higher cost performance [1][2][3]. However, mild steel also has some inherent weaknesses, such as low hardness and poor wear resistance, which cause a reduction in the suitable life of mild steel [4].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method of modifying metal and alloy surfaces to increase a variety of performance indicators is plasma electrolytic treatment [4][5][6][7]. There are a variety of processes aimed at obtaining ceramic-like coatings by plasma electrolytic oxidation [8][9][10][11][12][13][14] and surface polishing or removal of the surface layer by plasma electrolytic polishing (PEP) [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%